Kristallwachstum - Wachstum von Zinn-Whiskern im Raster-Elektronenmikroskop - Kehrer, H.-P.; Zaminer, Christian (IWF (Göttingen), 1972)
Whisker / Zinn
Zinn / elektronenmikroskopische Aufnahmen
Kristallwachstum / Zinn-Whiskern

whisker / tin
tin / electron microscopy
crystal growth / tin-whisker
Crystal Growth - Growth of Tin Whiskers in the Scanning Electron Microscope
Keywords: Engineering; Entstehung faden- und wulstförmiger Gebilde aus einer auf Cu elektrolytisch abgeschiedenen Sn-Schicht. Wachstum durch Materialzufuhr vom Fußpunkt, Whiskerbewegungen, Temperaturabhängigkeit der Wachstumsgeschwindigkeit. Zeitraffung.; Using a special time-laspe cinematographic technique and a speed of 11 frames per minute it was possible to record the growth of tin whiskers in a scanning-electron microscope. It will be noted that filament-type tin whiskers as well as bulbous shapes grow out ot the specimen which has been heated to 70° C and has an electroplated layer of tin on the surface, which is approximately 1 µm thick. It is apparent from the film that the growth of these whiskers is fed by material from the tin coating which moves upwards from the bottom of the coating. The swaying of the whiskers during growth, and the temperatured relation of the growth rate, become visible in ideal settings.